The 5E-based SPOC Instructional Approach on the ICVE Platform for Barista Training Courses - Dong, Zhihui; Li, Changhan (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: In the digital era, traditional single-method teaching approaches are increasingly insufficient to meet the demands of modern education. Therefore, this study integrates the traditional 5E instructional model with modern educational technology—the ICVE platform’s SPOC. It examines the impact of this approach on students’ academic performance and their acceptance of ICVE SPOC technology. By leveraging the 5E-based ICVE SPOC Instructional Approach, the study aims to refine teaching strategies, enhance instructional effectiveness, and improve the quality of talent cultivation in barista training courses. Materials and Methods: A quasi-experimental design was employed to evaluate students’ performance, including barista knowledge, customer service provision, coffee station organization, coffee preparation and serving, and an overall barista knowledge and skills score, to assess the impact of the 5E-based ICVE SPOC for Barista Training Courses. Additionally, based on the Technology Acceptance Model (TAM), a random sample of 15 students from the experimental group was selected to respond to open-ended questions evaluating their acceptance of the 5E-based ICVE SPOC instructional approach. Results: The implementation of the 5E-based ICVE SPOC instructional approach significantly improved students’ performance. Additionally, respondents generally held a positive attitude toward the ICVE SPOC, particularly appreciating its rich learning resources, convenient classroom activities, and timely learning feedback. Based on the TAM, under the guidance of the 5E instructional model, the SPOC functionality of the ICVE platform enhanced learners’ perceived usefulness (PU) and perceived ease of use (PEOU) by providing abundant course resources, convenient instructional activities, and timely learning feedback. Furthermore, the study also found that PU and PEOU significantly influenced participants’ attitudes toward technology (ATT) and behavioral intention (BI). Conclusion: This study confirms that the 5E-based ICVE SPOC instructional approach significantly enhances learning outcomes in barista training courses. The deep integration of the classic instructional model with modern intelligent teaching technologies will drive transformations in teaching methods, support vocational education classroom reform, and foster innovation in curriculum development.